Implementasi Komunikasi Pemasaran Melalui Event Berbagai Panggung Dalam Menarik Minat Pengunjung Di Berbagi Kopi Denpasar - Maria Septiana Rosana Dewi; I Nengah Wirata; Amirosa Ria Satiadji (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pariwisata Bali, 2022)
Currently, the development of the business world in Denpasar City is very significant. Companies must have a strong strategy to attract consumers and their target market. Berbagi Kopi Denpasar designed a strategy through the implementation of the Berbagi panggung event in attracting visitors. The type of event implemented is an art event. This study uses a type of approach that collected by observation, interviews, and documentation and analyzed with the stages of data reduction, data presentation, and drawing conclusions. The problem that will be analyzed in this research is limited by analyzing three-event approaches in the form of entertainment, excitement, and effort in implementing marketing communications through the Berbagi Panggung event in attracting visitors' interest at Berbagi Kopi Denpasar. The results of this study were the entertainment approach that was carried out by Berbagi Panggung through performers, each of which was different. The joyous approach was taken by the Berbagi Panggung to provide a memorable experience for visitors with the interactions that occurred between the performers and visitors. Enterprise is the readiness of the Berbagi Panggung in the risk that will occur and dare to do something new. The implementation of marketing communication through the event has been well implemented so that the event plays a role in attracting visitors to come to Berbagi Kopi Denpasar.